Approaches to Scaling Skill Intelligence Platforms - Viktoriia, Syrotenko (Human Resource and Leadership Journal, 2026)
Purpose: Skill Intelligence Platform (SIP) Support for hiring skills, mobility and learning. This conceptual document synthesizes empirical conclusions to identify SIP scalable and responsible approaches. Methodology: We have made an integrated overview of fifteen sources with skill extraction, oncology leveling, knowledge of knowledge and operation results. Studies have been carried out for HR relevance and clear data report, matrix and references. The evidence was coded on the map of evidence regarding data sources, algorithms, oncology, evaluation and life cycle control. Findings: Synthesis created five -emental structure (skill -5): Source integration, knowledge modeling, pipe estimates, life cycle engineering and logic and management. During a study, a hybrid pipe increases the pipeline combining weak supervision with large language models without losing accuracy. Improved portability ESCO/O*improved. The job skill chart allows comparison, mobility and course design. The Lups controls check including the shadow test, Canary and drift monitors. The main risks included distortion, whirling of the concept, drift of tongue and cost instability, Human loop drugs, audit trails and budget route reduced them. Unique Contribution to Theory, Practice and Policy: This study advances theory by transferring oncology-derived cumulative uncertainty modelling (CUM) and modular hybrid estimation into the HR analytics domain, improves practice by providing a scalable and disciplined framework for evaluating strategic intervention programmes (SIP) against measurable business outcomes, and informs policy by recommending standardized research intervals, multilingual benchmarking, automated evidence updates, and mandatory distortion audits to align analytical models with real workforce effects.